2019
DOI: 10.1093/mnras/stz2751
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the thermal Sunyaev–Zel’dovich effect and excess millimetre emission in quasar environments

Abstract: In this paper we probe the hot, post-shock gas component of quasar-driven winds through the thermal Sunyaev-Zel'dovich (tSZ) effect. Combining datasets from the Atacama Cosmology Telescope, the Herschel Space Observatory, and the Very Large Array, we measure average spectral energy distributions (SEDs) of 109,829 opticallyselected, radio quiet quasars from 1.4 GHz to 3000 GHz in six redshift bins between 0.3 < z < 3.5. We model the emission components in the radio and far-infrared, plus a spectral distortion f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 162 publications
(279 reference statements)
0
9
1
Order By: Relevance
“…Based on the observed highly ionized UV emission ratios, we rule out the presence of a dynamically important hot wind phase and place an upper limit on the pressure a hot wind may impart to the UV emitting clouds at 10 kpc. This upper limit is an order-of-magnitude lower than recent estimates based on tentative detections (3 − 4σ) of the Sunyaev-Zel'dovich effect around quasars at z ∼ 2 − 3 (Hall et al 2019;Lacy et al 2019). This tension can be reconciled if AGN feedback varies significantly from object-to-object (e.g.…”
Section: Discussioncontrasting
confidence: 54%
“…Based on the observed highly ionized UV emission ratios, we rule out the presence of a dynamically important hot wind phase and place an upper limit on the pressure a hot wind may impart to the UV emitting clouds at 10 kpc. This upper limit is an order-of-magnitude lower than recent estimates based on tentative detections (3 − 4σ) of the Sunyaev-Zel'dovich effect around quasars at z ∼ 2 − 3 (Hall et al 2019;Lacy et al 2019). This tension can be reconciled if AGN feedback varies significantly from object-to-object (e.g.…”
Section: Discussioncontrasting
confidence: 54%
“…While the primary objectives of eBOSS and other SDSS-IV programs informed the target selection for quasars in DR16Q (see Section 2.2), eBOSS quasar catalogs have been used in a number of other recent research studies beyond the eBOSS core programs. These include, but are certainly not limited to, the study of changing-look quasars, which can be used to investigate accretion mechanisms and other quasar physics (Sheng et al 2020); X-ray studies of the clustering of quasars, which can also give insight into the growth and evolution of supermassive black holes (Powell et al 2020); studies of the correlation between X-ray and emission-line luminosities (Timlin et al 2020); studies of quasar outflows in the far-infrared and radio bands via follow-up of optically confirmed quasars (Hall et al 2019); studies of the correlation of outflow velocities with bolometric luminosity in broad absorption-line (BAL) quasars (Bruni et al 2019); and studies of the variability in BAL troughs over time (Grier et al 2016;McGraw et al 2017). To help facilitate these sorts of quasar studies, DR16Q includes multiple redshift estimates, BAL and damped Lyα (DLA) quasar identifications, and compiled multiwavelength data.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical and observational works have suggested that the energy and momentum in galaxy outflows are shared between multiple phases of the gas. These gas phases span a wide range of densities and temperatures, from the dense cold molecular and neutral gas (T ∼ 10-300 K) to the diffuse hot postshock medium (T > 10 7 K; Crichton et al 2016;Hall et al 2019). There have been several studies of multiphase outflows in distant quasars focusing on individual systems (Vayner et al 2017;Brusa et al 2018;Herrera-Camus et al 2019) and studying the cold molecular and ionized gas phase in galactic outflows.…”
Section: Introductionmentioning
confidence: 99%